Sm(iii)[12-MCGa(III)shi-4] as a luminescent probe for G-quadruplex structures. Issue 12 (24th November 2017) - Rajczak, Ewa; Pecoraro, Vincent L.; Juskowiak, Bernard
Abstract : The luminescent anionic metallacrown Sm12-MC-4 exhibits similarity in shape and size to the guanine tetrad and is able to form complexes with G-quadruplex assembly. Abstract : G-quadruplexes (GQs), spatial assemblies of guanine-rich DNA strands, play an important role in the regulation of gene expression and chromosome stabilization. These structures are recognized to be useful in cancer therapies as the presence of multiple G-quadruplexes in a telomeric strand stops cancer cell proliferation. Metallacrowns of the type 12-MC-4 form planar structures that have remarkable similarity to G-tetrads in terms of dimension, shape and the ability to bind alkali metal and lanthanide cations in a central cavity. The interaction between the Sm(iii )[12-MCGa(III)shi -4] (SmMC) metallacrown (MC) and human telomeric G-quadruplex structures was examined using several methods including CD titrations, CD melting temperatures, fluorescence titration of SmMC with GQ/Na +, fluorescence intercalator displacement (FID) assays and methods measuring the MC quenching effect on the Tb 3+ /GQ luminescence. It was proven that the studied metallacrown acted as a sensing probe and interacted with quadruplex DNA. The Stern–Volmer quenching constant ( K as ) of Tb 3+ /GQ luminescence was calculated to be 3.9 × 10 5 M −1 . The binding constant using the indirect FID method gave the result of 1.3 × 10 5 M −1 . CD melting temperature experiments reveal the following pattern – the higher the concentration of the complex the lower the registered T m for quadruplex DNA, which indicates a destabilizing effect of SmMC at higher GQ : MC ratios. These data implicate a shape and size selective interaction between MCs and GQs that may be exploited for telomere detection.